Performance Analysis of the Behavior Based Safety Program in Reducing Occupational Accident Rates - Mitha Qurrota Ayuni; Muhammad Yusuf; Endang Dwiyanti (Universitas Airlangga, 2022)
Introduction: PT. X is a company that concentrates on the agricultural sector by producing ammonia and urea fertilizers. Occupational accidents at PT.X are reported and recorded by the Department of Occupational Health and Safety, one of which is a form of monitoring the performance of the BBS program at PT. X. The research objective was to determine the performance of the Behavior-Based Safety (BBS) program in reducing occupational accidents due to unsafe actions at PT.X. Methods: This study is an observational study. Determination and sampling in this study used accidental sampling technique for safety officers as many as 5 respondents, while the cluster sampling technique was used for the workforce of 95 respondents. The data analysis method used was descriptive semi-quantitative. Results: The results showed the fulfillment of the criteria and maturity level of behavior-based safety at PT. X, In general, PT X was already at level 4, namely